PELATIHAN BANTUAN HIDUP DASAR (BHD) AWAM UNTUK SISWA SMA - Rahman, Hilmah Noviandry Rahman; Syakura, Abdan; Hafidah, Lailatul; Suryadi A, Edy; Sari, Agoesta Pralita; Kuzzairi, Kuzzairi; Iva N, Cantika; Dian R, Nadia; Kristian T, Kristian T; Nur, Mohamad; Pujiani, Honesty; Iszakiyah, Nur; Fauziyah, Nur Aini; Suhendro, Prastomo; Yuliana W, Rahayu; Faizah, Anif Usni (LPPM Universitas Bina Bangsa, 2024)
Basic Life Support (BLS) is a set of skills used to maintain airway and circulation without using tools. It can be performed by anyone, including high school students, at any time and place. Unfortunately, many laypeople and students lack knowledge about basic life support. To address this issue, the author and their team conducted a community service program focused on providing basic life support training for students. The aim was to enhance students' knowledge and skills in administering emergency first aid effectively, enabling them to handle emergencies and save lives. This initiative is aligned with the vision and mission of the health department, particularly in dealing with maritime emergencies. The training methods included lectures and simulations, and the participants were assessed using a multiple-choice type closed-ended questionnaire. The respondents completed the questionnaire before the training (pre-test) and after the training (post-test). The data analysis revealed an average pretest score of 56.54 and a posttest score of 84.88. This analysis was conducted using Google Forms. Various factors influenced the participants' success, including their own initiative, interest, and enthusiasm in learning and retaining the training content. Overall, the participants demonstrated proficiency in handling victims and providing basic life support. However, certain aspects, such as the rescuer's position and readiness, need to be evaluated and emphasized, as they are often overlooked by participants